KATA-KATA TABU DALAM BAHASA INGGRIS DAN BAHASA JAWA TONDANO (SUATU ANALISIS KONTRASTIF) - SARONO, MAYANGSARI EDENIA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This research is entitled â€œTaboo Words in English and Javanese language: A Contrastiv Analysisâ€ . The objectives of this research are to identify, classify and analyze the types of taboo words. This research uses a descriptive method. There are three steps to finish this research, the first step is preparation, the data of taboo words in the English Language were taken from some books, films, and native speakers; while in Java language were taken from native speakers in Kampung Jawa Tondano. The second step the writer wrote on a piece of papers is the data about Java language, then the writer asked the meaning of taboo words to some informants as well as asked more info about taboo words. The third step is the data were analyzedÂ  using theory of Wardhaugh (1986:230) and were contrasted to find out similarities and differences using Lado theory. The results of this research show that there are 43 taboo words in English and 30 taboo words found in Java language and they were classified into five types, those are, sex, bodily function, animal, death, and religion. It also shows that the causes of using taboo words are to express the emotion, such as anger, happy, and surprises, to talk about sex, to joke and to insult. Keywords :Taboo Words; English and Javanese; ContrastiveAnalysis